Assessment of anti-HIV-1 guide RNA efficacy in cells containing the viral target sequence, corresponding gRNA, and CRISPR/Cas9 - Allen, Alexander G.; Chung, Cheng-Han; Worrell, Stephen D.; Nwaozo, Glad; Madrid, Rebekah; Mele, Anthony R.; Dampier, Will; Nonnemacher, Michael R.; Wigdahl, Brian (Frontiers in Genome Editing, 2023)
The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 gene editing system has been shown to be effective at inhibiting human immunodeficiency virus type 1 (HIV-1). Studies have not consistently used a trackable dual reporter system to determine what cells received the Cas9/gRNA to determine the overall knockdown of HIV. Some studies have used stably transduced cells under drug selection to accomplish this goal. Here a two-color system was used that allows tracking of viral protein expression and which cells received the CRISPR/Cas9 system. These experiments ensured that each gRNA used was a perfect match to the intended target to remove this variable. The data showed that gRNAs targeting the transactivation response element (TAR) region or other highly conserved regions of the HIV-1 genome were effective at stopping viral gene expression, with multiple assays demonstrating greater than 95 percent reduction. Conversely, gRNAs targeting conserved sites of the 5’ portion of the U3 region were largely ineffective, demonstrating that the location of edits in the long terminal repeat (LTR) matter with respect to function. In addition, it was observed that a gRNA targeting Tat was effective in a T-cell model of HIV-1 latency. Taken together, these studies demonstrated gRNAs designed to highly conserved functional regions have near 100% efficacy in vitro in cells known to have received the Cas9/gRNA pair.